2022
DOI: 10.48048/tis.2022.3063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Traditional Thai Massage on Quality of Sleep in Adults with Sleep Problem

Abstract: Sleep problem or insomnia is one of the most common causes of health problems, affecting around 10 - 20 % of the world population. Traditional Thai massage (TTM) is a popular alternative treatment in Thailand for reducing fatigue and improving sleep quality. This study aimed to examine the effect of traditional Thai massage on sleep quality in adults. Twenty-eight adults with poor sleep quality (based on Verran and Snyder-Halpern sleep scale) participated. They were randomly allocated into a control group (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The combination of effleurage and friction techniques will trigger the release of endorphins, serotonin, and dopamine hormones that are beneficial to the body, by providing calmness, reducing pain or soreness [18], so that physiologically it can improve sleep quality. This research is in line with research [19] entitled "The effect of traditional Thai massage on quality of sleep in adults with sleep problems" that the treatment given can improve sleep quality and reduce fatigue significantly without side effects, and research [20] entitled "Effect of mechanicalbed massage on exerciseinduced back fatigue in athletes" concluded that massage treatment can help athletes overcome fatigue due to exercise, by modulating sympathetic and parasympathetic nervous system activity. Calculation of data analysis shows the results of improving sleep quality and reducing the level of fatigue of postCO-VID19 workers with a significance value of 0.00 < 0.05 in the paired ttest analysis, in indicators of fatigue and sleep quality.…”
Section: Discussionsupporting
confidence: 79%
“…The combination of effleurage and friction techniques will trigger the release of endorphins, serotonin, and dopamine hormones that are beneficial to the body, by providing calmness, reducing pain or soreness [18], so that physiologically it can improve sleep quality. This research is in line with research [19] entitled "The effect of traditional Thai massage on quality of sleep in adults with sleep problems" that the treatment given can improve sleep quality and reduce fatigue significantly without side effects, and research [20] entitled "Effect of mechanicalbed massage on exerciseinduced back fatigue in athletes" concluded that massage treatment can help athletes overcome fatigue due to exercise, by modulating sympathetic and parasympathetic nervous system activity. Calculation of data analysis shows the results of improving sleep quality and reducing the level of fatigue of postCO-VID19 workers with a significance value of 0.00 < 0.05 in the paired ttest analysis, in indicators of fatigue and sleep quality.…”
Section: Discussionsupporting
confidence: 79%
“…Field workers frequently report disrupted sleep patterns due to work fatigue, resulting in decreased sleep quality. To alleviate fatigue and enhance sleep quality, workers often address their physical condition by resting, using traditional herbal remedies, and seeking massage therapy (Chompoopan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%